(untitled) (Nordic Journal of African Studies, 2004)
Taarab is a music complex that demonstrates the fusion of local elements and those from Arabia, Europe, India, the USA, and Afro-Cuban. Until recently, the taarab lyric has been normally composed following prosodic rules found in Arabic poetry and written to portray mainly ’romanticized love’. In a taarab sub-category called mipasho conceived in the 1990s, the form, shape and function of the taarab lyric have changed radically. The lyric is now often composed in blank and free verse styles, about anything that opiates and expresses wishful thinking based on consumerism and rivalry between individuals and groups. This essay sets out to show the type of images the Swahili poets use to constructs many facets of love in the taarab lyric in its traditional and modern form. Initially, this essay was presented as a paper in a colloquium jointly organised by the Department of Islamic Studies and the Professorship of the African Literatures in African languages of the Bayreuth University (Universität Bayreuth) in May 2003, in one of international meetings organized to provide discussion of various interdisciplinary topics under the umbrella project "Local Action in the Context of Global Influences" sponsored by the Humanities Collaborative Research Centre (Kulturwissenschaftliches Forschungskolleg - SFB/FK560).